Phytochemical Analysis of Mangrove Leaf Extract Lumnitzera racemosa as a Potential Source of Bioactive Compounds - Fakhrurozi Fakhrurozi; Irwan Effendi; Nursyirwani Nursyirwani; Ronal Kurniawan (Science, Technology, and Education Care, 2026)
This study was conducted to identify the secondary metabolite prile in the leaf extract of Lumnitzera racemosa, which has potential as a natural antibacterial agent. Leaf samples were collected from the mangrove area of Pecinta Alam Bahari (PAB), Dumai City, and extracted with 96% ethanol using a maceration method. Phytochemical tests were conducted qualitatively on seven groups of compounds, namely alkaloids, flavonoids, phenolics, saponins, tannins, triterpenoids, and steroids. Analysis revealed the presence of flavonoids, phenolics, and triterpenoids, while alkaloids, saponins, tannins, and steroids were not detected. The identified compounds have different antibacterial mechanisms but are effective in disrupting the structure and function of bacterial cells. These findings suggest the potential of L. racemosa leaf extract as a source of bioactive compounds for health and aquaculture applications.